CONCEPTUAL BASIS OF TRAINING FUTURE TEACHERS-TRANSLATERS - Sevinch Bakhtiyorova (European Science Publishing, 2024)
The article discusses the conceptual foundations of training future pedagogues-translators in the process of higher pedagogical education and presents the author's individual approaches to the issue.
Keywords: pedagogue and translator, higher education and training, English and teacher, conceptual framework, purpose and scope.